Pattern of Mechanical Asphyxia Deaths in Forensic Autopsies at Medicolegal Section of Liaquat University Hospital, Hyderabad: Mechanical Asphyxia Deaths in Forensic Autopsies - Aslam, Nadia; Bibi, Ishrat; Shaikh, Muhammad Rafique; Munir, Ummara; Pal, Mobin Inam; Samad, Abdul (Pakistan Journal of Health Sciences, 2024)
Asphyxia is characterized by oxygen deprivation in cells resulting from insufficient or altered oxygen supply. Mechanical asphyxia refers to inadequate breathing caused by external forces. This study assessed the pattern of mechanical asphyxia-related autopsies carried out at a medico-legal section of Liaquat University Hospital, Hyderabad. Objective: To assess the pattern of mechanical asphyxia-related autopsies carried out at a medico-legal section of a tertiary care teaching hospital. Methods: This prospective observational study was performed to analyze the forensic autopsy reports from January 2021 to December 2022 at Liaquat University Hospital. Hyderabad and 103 medico-legal cases of mechanical asphyxia were enrolled. All autopsy reports related to mechanical asphyxia were included. The data were collected on a predesigned pro forma. Autopsies of non-medicolegal nature and related to unnatural deaths apart from mechanical asphyxia were excluded. Results: Most of the cases (n=51) were identified as caused by the drowning. The hanging and strangulation occurred in an equal number of mechanical asphyxia-related autopsies (n=26 each). The male gender dominated the frequency of drowning and strangulation while hanging was more prevalent in females. Conclusions: Drowning was observed as the most prevalent mechanism of mechanical asphyxia in medico-legal autopsies conducted over a period of two years